On the Performance of a Miniaturized Reactive Loaded Monopole Antenna for Ex Vivo Catheter Applications - Debarati Ganguly; Jogesh Chandra Dash; Debdeep Sarkar (IEEE Access)
In this paper, we propose a miniaturized series L-C loaded monopole antenna for catheter application in microwave ablation systems. Initially, a quarter wavelength long monopole antenna (Design1), having length 30 mm ( $≈ 0.24λ _{0}$ where $λ _{0}$ represents the free-space wavelength at 2.4 GHz operating frequency) using series LC loading concept is designed. The initial design is further extended to a miniaturized version (Design2) having length 5 mm ( $≈ 0.04λ _{0}$ ), showing nearly 83% size reduction compared to its former.Both the antennas are designed and simulated by immersing inside high permittivity egg white phantom ( $ε _{r}$ = 63.84). Antenna Design 1 and 2 exhibit good impedance matching ( ${S_{11} < -12}$ dB) at and around the operating frequency with uniform monopolar radiation pattern having co-to-cross isolation of nearly 30–35 dB. Further, the in-phantom Specific Absorption Rate (SAR) values for both antennas are evaluated using simulation and verified with the measured SAR values such as 22 W/kg and 19.6 W/kg for Design1 and 2 respectively, using an in-house experimental setup. Moreover, the microwave ablation property of the proposed antennas is studied using simulated transient thermal gradient which translates to ablation zone formation. Here, Design 2 shows the advantage of having a low invasive diameter of 1.5 mm and near unity aspect ratio (AR) for the ablation zone as compared to Design1.